La literatura notarial castellana durante el siglo XVI y su difusión en América - Reyes Rojas García (Nuevo mundo - Mundos Nuevos, 2012)
Formularies are one of the fundamental pillars for the trainning of the notary public, because they provide a wide variety of very useful notarial documents as a guide for them. Besides, these works are a standard for notarial practice. Formulary is a vital reference work because, throughout the Sixteenth century, compiles important information on notarial practice and procedure. Gradually they are including new documents according to the latest requirements of the society. Most of these works are created in the Castilian Crown, but during the Sixteenth Century they reach America, reproducing the models of the metropolis. Despite this, the American notary will develop their own differences and peculiarities.